Fabrication of (Ni, S)-Codoped ZnO Nanophotocatalysts as Efficient Solar-Light Driven Photocatalysts for the Degradation of Organic Azo Dyes in Aqueous Media - D. Sonia; E K Kirupa (Journal of Water and Environmental Nanotechnology)
In this study, a visible-light-active undoped ZnO and (Ni, S)-codoped ZnO photocatalyst was synthesized in nano form using the co-precipitation method with ZnSO₄•7H₂O as a precursor. The structural and morphological properties of the synthesized photocatalyst were analyzed through spectroscopic methods, including XRD, FT-IR, SEM-EDAX, TEM, and UV-DRS analyses.  The photocatalytic activity of the synthesized materials was tested on an azo dye, Direct Red-81 and its degradation efficiency was evaluated.    The results revealed that 100% of Direct Red-81 azo dye was degraded using (Ni, S)-codoped ZnO photocatalysts (0.1 g/100 mL) under visible light irradiation within 20 minutes. Moreover, 99% mineralization was confirmed using COD and TOC analyses.   The reaction rate followed pseudo-first-order kinetics with a rate constant of 0.064 × 10⁻³ min⁻¹. Furthermore, the photocatalysts demonstrated reusability and were effective for eight consecutive cycles without any loss in efficiency. These findings illustrate the enhanced photocatalytic activity of the (Ni, S)-codoped ZnO photocatalyst, which is attributed to the reduced rate of electron-hole recombination reactions. Additionally, the synthesized nanoparticles were eco-friendly, stable, and well-organized, making them suitable for the treatment of industrial and agricultural wastewater containing organic contaminants in relatively shorter periods under sunlight irradiation. Hence, the synthesized (Ni, S)-codoped ZnO photocatalyst serves as a significant tool for the treatment of effluents in various environmental applications.